MINERO: Penyuluhan Pembuatan Mineral Blok sebagai Upaya Pemenuhan Kebutuhan Mineral Ternak Ruminansia - Syahrani Guslatifah; Aira Azalia Putri; Dinur Ahmada; Elin Ardiana; Indah Feronika; Muhammad Alvian; Rhizka Alifia Maryadinnisa; Wicky Surya Phentagon (Jurnal Pusat Inovasi Masyarakat, 2026)
Minerals are needed in the bodies of ruminant livestock for food metabolism by rumen microbes. Mineral deficiency can be a problem for the growth and development of young ruminants. Mineral blocks are one of the alternative feed supplements that are currently being developed to maintain the balance of mineral requirements in ruminant feed. The mineral block production outreach program aims to increase knowledge, skills and interest of farmers in Ponolawen Village in meeting the mineral requirements of livestock by providing mineral blocks. The methods used in implementing this program were direct surveys of farms, direct interviews, distributing invitations to farmers in Ponolawen Village, providing outreach services by giving materials related to the definition and benefits of mineral blocks and how to make them, and ending with a demonstration of how to make mineral blocks. This outreach activity was attended by 11 goat farmers with a total of around 80 goats. The evaluation of the activity was conducted using the AIDA (Attention, Interest, Desire, Action) model approach. This outreach activity hopefully provided farmers with knowledge, skills, and interest to make mineral blocks independently and experience direct benefits for their livestock. The training on mineral block production is a long-term investment for livestock welfare. It is recommended that similar training be continued with the support of publications, monitoring, and evaluation that can involve the wider village community to ensure the sustainability of the program.